1980
DOI: 10.1111/j.1755-3768.1980.tb08324.x
|View full text |Cite
|
Sign up to set email alerts
|

Central Corneal Thickness and Intraocular Tension in Patients With Acromegaly

Abstract: In 27 patients with pituitary adenomas the central corneal thickness and the intraocular tension were measured. Thirteen of the patients were suffering from acromegaly, and in this group the central corneal thickness was 0.561 mm +/- 0.35 (mean +/- SD). In the 14 patients with pituitary adenomas but no acromegaly the central corneal thickness was 0.526 mm +/- 0.030 (mean +/- SD). This difference is statistically significant 0.01 greater than P greater than 0.001. In the 13 patients with acromegaly the intraocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 8 publications
2
19
0
3
Order By: Relevance
“…This is supported by the fact that when IOP was corrected for CCT according to the formula proposed by Doughty and Zaman [18], no significant IOP difference could be detected between acromegalic and healthy subjects. Our results corroborate findings by Bramsen et al [12]. The authors investigated GAT readings and CTT measurements obtained with optical pachymetry in patients with pituitary tumors with (n=13) and without acromegaly (n=14).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This is supported by the fact that when IOP was corrected for CCT according to the formula proposed by Doughty and Zaman [18], no significant IOP difference could be detected between acromegalic and healthy subjects. Our results corroborate findings by Bramsen et al [12]. The authors investigated GAT readings and CTT measurements obtained with optical pachymetry in patients with pituitary tumors with (n=13) and without acromegaly (n=14).…”
Section: Discussionsupporting
confidence: 80%
“…Published evidence to date has indicated that IOP is significantly increased in acromegalic patients when compared with healthy subjects [12,14,27]. Consequently, acromegaly has been considered a risk factor for glaucoma development [10,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased corneal thickness, pigmentary degeneration of the retina, melanocytic tumours of the choroid, enlarged extraocular muscles, proptosis, and total ophthalmoplegia are some of the ocular manifestations of acromegaly. [6][7][8][9][10][11] On the other hand, there is a gap in the literature about the impact of acromegaly on the fovea, optic nerve head, and choroid.…”
Section: Introductionmentioning
confidence: 99%